Elemental stoichiometry indicates predominant influence of potassium and phosphorus limitation on arbuscular mycorrhizal symbiosis in acidic soil at high altitude - Khan, Mohammad Haneef (Journal of plant physiology, 2015)
Copyright © 2015 Elsevier GmbH. All rights reserved.